High Cell Density Perfusion Culture has a Maintained Exoproteome and Metabolome. Issue 10 (13th July 2018) - Zamani, Leila; Lundqvist, Magnus; Zhang, Ye; Aberg, Magnus; Edfors, Fredrik; Bidkhori, Gholamreza; Lindahl, Anna; Mie, Axel; Mardinoglu, Adil; Field, Raymond; Turner, Richard; Rockberg, Johan; et al.
Abstract : The optimization of bioprocesses for biopharmaceutical manufacturing by Chinese hamster ovary (CHO) cells can be a challenging endeavor and, today, heavily relies on empirical methods treating the bioreactor process and the cells as black boxes. Multi‐omics approaches have the potential to reveal otherwise unknown characteristics of these systems and identify culture parameters to more rationally optimize the cultivation process. Here, the authors have applied both metabolomic and proteomic profiling to a perfusion process, using CHO cells for antibody production, to explore how cell biology and reactor environment change as the cell density reaches ≥200 × 10 6 cells mL −1 . The extracellular metabolic composition obtained in perfusion mode shows a markedly more stable profile in comparison to fed‐batch, despite a far larger range of viable cell densities in perfusion. This stable profile is confirmed in the extracellular proteosome. Furthermore, the proteomics data shows an increase of structural proteins as cell density increases, which could be due to a higher shear stress and explain the decrease in cell diameter at very high cell densities. Both proteomic and metabolic results shows signs of oxidative stress and changes in glutathione metabolism at very high cell densities. The authors suggest the methodology presented herein to be a powerful tool for optimizing processes of recombinant protein production. Abstract : Producing therapeutic proteins in perfusion reactors has many advantages compared to fed‐batch systems, for example, higher product quality and extended cultivation periods at higher cell densities. Here, supernatant samples are collected from a perfusion reactor for metabolomics and proteomics analysis over a 45 day cultivation, during which the cell density of antibody‐producing CHO cells reached the extremely high viable cell density of >200 million viable cells per milliliter. The study showed that the biologic content in the perfusion reactor is stable up to very high cell densities, which encourages production at higher densities than what is typically used.